Peran Kepemimpinan dan Kedisiplinan Melalui Pengawasan Untuk Meningkatkan Kinerja di Industri Otomotif - Ahmad Nizar Yogatama; Robby Himawan Giri (Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine the role of leadership and discipline on performance through supervision at PT. Prosperous with Motor. This is because the company is the official sales and maintenance branch of Honda cars in the Probolinggo and Pasuruan area which has a vision of entering the 10 branches with the most Honda car sales in East Java in 2020. The method used in this research is descriptive and correlational using path analysis. This study uses a questionnaire to get answers about this research from respondents. The population was taken from all employees of PT. Prosperous with Motorcycles as many as 75 people. While the samples obtained in this study were 75 respondents. In this study using a nonprobability sampling technique, namely the census technique. The results showed that leadership and discipline on employee performance through supervision had a positive impact. However, the results achieved were not optimal due to ineffective communication.